Assessment of cardiac recovery in patients supported with venoarterial extracorporeal membrane oxygenation. (22nd April 2022) - Vuthoori, Ravi; Heaney, Cassandra; Lima, Brian; Knisel, Alexis; Miller, Ed; Kennedy, Kevin; Majure, David; Stevens, Gerin; Bocchieri, Karl; Cassiere, Hugh; Fernandez, Harold; Maybaum, Simon
Abstract: Aims: Venoarterial extracorporeal membrane oxygenation (VA‐ECMO) is increasingly being used to support patients in cardiogenic shock (CS). Early determination of disposition is paramount, as longer durations of support have been associated with worse outcomes. We describe a stepwise, bedside weaning protocol to assess cardiopulmonary recovery during VA‐ECMO. Methods and results: Over 1 year, we considered all patients on VA‐ECMO for CS for the Weaning Protocol (WP) at our centre. During the WP, patients had invasive haemodynamic monitoring, echocardiography, and blood gas analysis while flow was reduced in 1 LPM decrements. Ultimately, the circuit was clamped for 30 min, and final measures were taken. Patients were described as having durable recovery (DR) if they were free of pharmacological and mechanical support at 30 days post‐decannulation. Over 12 months, 34 patients had VA‐ECMO for CS. Fourteen patients were eligible for the WP at 4–12 days. Ten patients tolerated full flow reduction and were successfully decannulated. Twenty‐four per cent of the entire cohort demonstrated DR with no adverse events during the WP. Patients with DR had significantly higher ejection fraction, cardiac index, and smaller left ventricular size at lowest flow during the WP. Conclusions: We describe a safe, stepwise, bedside weaning protocol to assess cardiac recovery during VA‐ECMO. Early identification of patients more likely to recover may improve outcomes during ECMO support.